Psychological skills for football players - Konter, E.; Beckmann, J.; Mallett, C. J. (Football Psychology - From Theory to Practice, 2019)
The chapter addresses a number of issues related to psychological skills and performance in football. Well-developed physical, technical, and tactical competencies are necessary but not sufficient prerequisites for success in modem football. Research indicates that the most successful athletes consistendy require and employ psychological skills to enhance performance (e.g. relaxation, imagery, goal setting, self-talk). Thus, psychological skills training should be part of training and practice in football. Despite an increasing acknowledgement of the importance of psychological skills for success in football, a systematic integration of sport psychological services into football still meets resistance. Some of this resistance is due to a lack of knowledge of football staff and coaches. To provide a communicable structure of psychological support, a three-level model of sport psychological support was proposed (Beckmann & Elbe, 2015). The model differentiates basic training (relaxation), psychological skills training, and conflict management. As a basic requirement psychological assessment is integrated into the model to adapt psychological skills training to the needs of the individual player. Psychological skills can be combined and integrated into routines that are also addressed in this chapter. Currently, the numerous psychological skills that have been developed across different sports need to be adapted to the specific demands of football. Promising first attempts to integrate psychological skills into holistic football-specific programmes are presented.